The experience of registered nurses nursing in the general audit intensive care unit - E. Pope; E. Nel; M. Poggenpoel (AOSIS, 1998)
In this article a phenomenological qualitative research study is discussed. More attention will be given to the methodology of the research. The objectives of the study are two-fold: firstly to explore and describe the experience of registered nurses nursing in the adult intensive care unit (this is the first phase of the research) and to describe guidelines based on the information obtained in the first phase to support the nurses in the form of a support programme in the second phase. The units of research are the registered nurses in the intensive care unit. The characteristics of the unit of research led to the emergence of a qualitative phenomenological research design of an explorative, descriptive and contextual nature. In the discussion of research methodology attention will be given to phase one: data gathering (ethical considerations and informed consent; purposive selection, phenomenological interviews and field notes); data analysis (Tesch's method of data analysis, methods to ensure trustworthiness, organisation of raw data and integration of findings supported by literature. Five themes were identified through the data analysis: impaired communication with management; discrimination: white on black racism; lack of fair, competitive remuneration and disregard for professional worth; non-conducive physical environment, and stressful working environment. Phase two: Guidelines were described to support the registered nurses in the intensive care unit based on the information obtained in phase one of the research.